2021
DOI: 10.5194/acp-2021-402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of rainfall-induced diabatic heating over southern China on the formation of wintertime haze on the North China Plain

Abstract: Abstract. During the winters (December–February) between 1985 and 2015, the North China Plain (NCP) suffered many periods of heavy haze, and these episodes were contemporaneous with extreme rainfall over southern China; i.e., South Rainfall−North Haze events. The formation of such haze events depends on meteorological conditions, which are controlled by the atmospheric circulation associated with rainfall over southern China, but the underlying physical mechanism remains unclear. This study uses observations a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, it is well known that the wet deposition through scavenging by rainfall is an effective way to remove atmospheric aerosols and soluble gases (e.g., Atlas and Giam, 1988). When the NAAA appears, southern China tends to experience heavy rainfall and vice versa in the NCP (not shown) (e.g., Ma et al, 2018;An et al, 2020An et al, , 2021, which is only not conducive to the wet removal of aerosol in the NCP, but usually deteriorates air quality in the NCP via a local north−south circulation (not shown) (An et al, 2020(An et al, , 2021Mei et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is well known that the wet deposition through scavenging by rainfall is an effective way to remove atmospheric aerosols and soluble gases (e.g., Atlas and Giam, 1988). When the NAAA appears, southern China tends to experience heavy rainfall and vice versa in the NCP (not shown) (e.g., Ma et al, 2018;An et al, 2020An et al, , 2021, which is only not conducive to the wet removal of aerosol in the NCP, but usually deteriorates air quality in the NCP via a local north−south circulation (not shown) (An et al, 2020(An et al, , 2021Mei et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Moreover, Cai et al (2017) found that global warming will further increase the incidence of haze days in China by reducing the wind strength. Specific to air pollution in the NCP, previous studies have found many influence factors, including sea surface temperature (Chang et al, 2016;Jeong et al, 2018;Yu et al, 2020), Arctic sea-ice (Wang et al, 2015, Zou et al, 2020, Eurasian snow cover and soil (Zou et al, 2017;Yin et al, 2018) and climate internal variability including the Eurasian Teleconnection (Li et al, 2019) and subtropical westerly jet waveguide (An et al, 2020(An et al, , 2021Mei et al, 2021), and so on. As a matter of fact, the northeast Asian anomalous anticyclone (NAAA) is directly related to air pollution in the NCP Callahan and Mankin, 2020).…”
Section: Introductionmentioning
confidence: 99%